Population Biology of Nile tilapia (Oreochromis niloticus) in Lake Naivasha, Kenya. Issue 2 (18th May 2020) - Waithaka, Edna; Yongo, Edwine; Outa, Nicholas; Mutethya, Eunice
Abstract: The Nile tilapia ( Oreochromis niloticus ) was introduced into Lake Naivasha to provide exploitable fisheries, being one of the commercially important fish providing livelihoods to communities around the lake. Its stocks in the lake have been declining, however, because of intense fishing, ecological changes and effects of other exotic species. The present study was undertaken to investigate the population and biological parameters of Oreochromis niloticus . Fish samples (1, 021) were caught monthly from January to December 2017, collecting a total of 1, 021 O. niloticus, with an overall sex ratio of 2.21:1.0 (male: female). The length of the fish ranged from 9.0 to 40.0 cmTL and weighed between 20 and 1, 220 g. The mean length and weight for all fish was 22.6 cm and 272.6 g. The slope b of length–weight relationship was 2.86 for all fish, indicating negative allometry. The mean condition factors were 0.99, 1.04 and 1.01 for male, female and all fish, respectively. The length at first maturity (Lm50 ) was estimated to be 28.0 cmTL for all sexes, indicating the fish matures at smaller sizes. The length at first capture (Lc50 ) was calculated to be 19.38 cm, a value much lower than its Lm50, reflecting the capture of juvenile fish. The asymptotic length ( L∞ ) was 42 cm, the growth coefficient ( K ) was 0.21/year, and the growth performance index (Ф) was 2.57. The natural ( M ), fishing ( F ) and total mortality ( Z ) coefficients were estimated to be 0.55, 0.26 and 0.80/year, respectively. The optimum sustainable yield (E 0.5 ), maximum sustainable yield ( E max ) and maximum economic yield ( E 0.1 ) indices of 0.23, 0.35 and 0.26, respectively, imply an optimal exploitation of O. niloticus . The results of the present study provided some important insights into the biology and management needs of the O. niloticus fishery in Lake Naivasha, as well as revealing a gap for further research on its reproductive biology.